The Effect of Increased Protein Intake During the Starter and Prebreeder Periods on Reproductive Performance of Ultra High Yield Broiler Breeder Hens - Beer, Marc de; Coon, Craig N. (International Journal of Poultry Science, 2006)
This study evaluated the provision of additional protein to broiler breeder pullets during the starter and prebreeder phases and its effect on production. The effect of lower body weight during rearing was also evaluated. Pullets were fed to reach breeder recommended target weights (H) or to be approximately 90 g smaller (L) than targets. Groups of H pullets were fed starter rations (19% CP) for one (H5) or two (H6) extra weeks and then according to breeder guidelines. Separate groups of H pullets were fed a 17% CP (HHP) or 14% CP (HLP) prebreeder diet from 16 to 21 weeks. Groups of L pullets were fed a 17% CP (LHP) or 14% CP (LLP) prebreeder from 16 to 21 weeks. Frame size and carcass protein was increased and carcass fat reduced in H5 and H6 during early rearing but differences dissipated. By the onset of lay no differences existed in carcass fat, protein or ash percentages. Egg production at 65 weeks of H5 and H6 groups was marginally improved as was HHP and LHP, although none differed significantly from H. Egg production of LLP was lowest (P< 0.05). H and HHP groups had the highest egg weights with L and LLP the lowest. Early stimulation of growth and frame size by providing additional protein gave moderate improvements in performance as did higher protein prebreeder diets. Lower than normal protein intake during the prebreeder phase resulted in reduced performance. L hens performed equivalently to H hens in all areas but egg size.